Perceived Challenges Facing Tourist Guides in South Africa - Matome G. Kapa; Engela P. de Crom; Uwe P. Hermann (African Journal of Hospitality, Tourism and Leisure, 2023)
This paper aims to evaluates different opinions to understand what tourist guides of South Africa would like to change about their guiding profession, addresses the challenges they face and what tourist guides should be expected to do. A non-random sample of 320 tourist guides was selected to participate in the study. Both qualitative and quantitative methodologies were used in conjunction for this investigation. An online questionnaire on which open-ended questions were posed to respondents. These responses were then analysed using content analysis which revealed the changes or improvements the respondents would like to see in the guiding industry to solve challenges facing the guiding industry. Key issues emerged from the study include the demand from tourist guides to have their industry licensed and regulated, paid better salaries, have regular training and workshops, lastly policing of unregistered and illegal tourist guides. The findings of this research make a contribution to the discourse in the field of tourist guiding in South Africa and internationally. The results of this research, the first of its kind in South Africa and limited internationally support and extend existing knowledge, as well as contribute to the understanding of tourist guiding. This study may assist in enhancing the discourse around the development and amendment of regulatory frameworks governing the guiding industry.